Smart Legal Mechanisms for Sustainable Cities - Cartaxo, Tiago de Melo (2018)
Cartaxo, T. D. M., Neto, M. D. C. S. F., & Vassalo, V. (2017). Smart Legal Mechanisms for Sustainable Cities. In Ö. Çınar (Ed.), Book of Proceedings of The 3rd International Conference on Sustainable Development (ICSD) 19-23 April 2017, Sarajevo (pp. 165-170). ICSD.